Ethic In Student Life : Social Media Ethics / Muhammad Haziq Ammar Imran ...[et al.] - Imran, Muhammad Haziq Ammar; Sulaiman, Muhammad Hafiz; Noor Azman, Nurul Izzati; Ali, Nurul Husna; A Sata, Nur Sabrina Ariesha (2019)
According to Stanford Encyclopedia of Philosophy by Social Networking and Ethics, most people live by their own morals and ethics and we all have our own belief as to what is right and wrong in life. Social networking is where some may feel that they are hiding behind a computer or phone screen and typing the words instead of speaking to the person personally, it really doesn't count as unethical behavior. Applications are growing day by day, almost every years there always have the new applications that we can apply on our daily basic. As technology becomes modem, people start to realize the different things we can do when incorporating social media into education, the connection and expansion of materials that we gain from it. We are taught as we grow up through face to face interactions, experiences and lessons where what we should and should not do. In this report, those will be shown about the social media ethics problems that most students of Uitm Pasir Gudang are less practices it on their online routine.